Integrative analysis of 5-methylcytosine associated signature in papillary thyroid cancer - Ying Ding; Xinying Li; Wenlong Wang; Lei Cai (Scientific Reports)
Abstract Emerging evidence has indicated that m5C modification plays a vital role in cancer development. However, the function of m5C-lncRNAs in PTC has never been reported. This study aims to explore the regulation mechanism of m5C RNA methylation-related long noncoding RNAs (m5C-lncRNAs) in papillary thyroid cancer (PTC). Bioinformatics analysis was used to investigate the role of m5C-lncRNAs in the prognosis and tumor immune microenvironment of PTC. Subsequently, we preliminarily verified the regulation mechanisms of m5C-lncRNAs in vivo and in vitro experiments. A total of six m5C-lncRNAs and five immune cell types were selected to construct the risk score and immune risk score (IRS) model, respectively. Patients with a high-risk score had a worse prognosis and the ROC indicated a reliable prediction performance (AUC = 0.796). As expected, the ESTIMATE and immune scores were higher (P < 0.001) and the tumor purity (P < 0.05) was significantly lower in the low-risk subgroup. CIBERSORT analysis showed Tregs, M0 macrophages, dendritic cells resting, and eosinophils were positively correlated to the risk score. Moreover, the expression levels of PD-1, PD-L1, CTLA-4, TIM-3, LAG-3, and KLRB1 were lower in the high-risk subgroup. Importantly, patients in high-risk subgroup tended to have a better response to immunotherapy than those in low-risk subgroup (P = 0.022). Similar to the above risk score, the IRS model also showed favorable prognosis predictive performance (AUC = 0.764). An integrated nomogram combining risk score, IRS, and age exhibited good prognostic predictive performance. Additionally, we validate the downregulation of PPP1R12A-AS1 promotes proliferation and metastasis by activating the MAPK signaling pathway. Our research confirms that m5C-lncRNAs not only contribute to evaluating the prognosis of patients with PTC but also help predict immune cell infiltration and immunotherapy response.